Solve for g y=gx+a

Math
y=gx+a
Rewrite the equation as gx+a=y.
gx+a=y
Subtract a from both sides of the equation.
gx=y-a
Divide each term by x and simplify.
Tap for more steps…
Divide each term in gx=y-a by x.
gxx=yx+-ax
Cancel the common factor of x.
Tap for more steps…
Cancel the common factor.
gxx=yx+-ax
Divide g by 1.
g=yx+-ax
g=yx+-ax
Move the negative in front of the fraction.
g=yx-ax
g=yx-ax
Solve for g y=gx+a

Meet the Team our Math Expers

Our Professionals

Robert Kristofer

Anna Frok

Magnus Flores

Lydia Fran

We are MathExperts

Solve all your Math Problems: https://elanyachtselection.com/

We can solve all your math problems
Scroll to top